Pengaruh Current Ratio, Return On Equity dan Debt To Equity Ratio Terhadap Harga Saham (Pada Perusahaan Konstruksi Bangunan di Bursa Efek Indonesia Periode Tahun 2014-2023) - Rukmana, Azlina Nur Fitriani; Merliana, Vina (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
This study aims to determine and explain the effect of Current Ratio, Return on Equity and Debt To Equity Ratio on Stock Prices in Building Construction companies listed on the Indonesia Stock Exchange for the 2014-2023 Financial Report Period with a sample of 7 companies. The research method used is quantitative with a descriptive and verification approach. Descriptive Statistical Analysis consists of Maximum Value, Minimum Value, Mean and Standard Deviation. The results of the descriptive analysis show that construction stock prices tend to decline during 2014-2023, while the financial ratios studied fluctuate and in 2020 tend to decline sharply. Verification Statistical Analysis consists of Classical Assumption Test and Multiple Linear Regression Test. Based on the results of partial hypothesis testing (t-test), the results obtained Current Ratio has no effect on Stock Price, while Return on Equity and Debt to Equity Ratio have an effect on Stock Price. While the simultaneous test through the F test, there is a simultaneous effect of Current Ratio, Return on Equity and Debt To Equity Ratio on Stock Price. Thus, the financial ratio determines investor decisions, thus affecting changes in stock prices. The absence of the Current Ratio indicates the characteristics of a building construction company where the Current Ratio cannot be used as a benchmark for increasing stock prices. Investors prefer long-term financial performance compared to short-term.